The Influence of Conflict Management Style on the Satisfaction of Student Institution Management - Saleh, Sirajuddin; Karaeng, Juliani; Akib, Haedar (Journal of Social Science and Economics (JOSSE), 2024)
The conflict management style in the organization is a management strategy in dealing with conflicts that occur. The use of an appropriate conflict management style will have a good impact on the organization. This study aims to find out the influence of conflict management style on the satisfaction of student institution administrators at the Faculty of Social Sciences and Law, Universitas Negeri Makassar. This study is a quantitative research that shows cause and effect. The sample in this study was 82 people with the Simple Random Sampling technique and 5 informants. The data collection techniques used are observation, questionnaires, interviews, and documentation. The data analysis techniques used are descriptive data analysis and inferential statistical analysis. The results of the study show that the conflict management style of student institutions at the Faculty of Social Sciences and Law, Universitas Negeri Makassar is in the "Good" category with 5 indicators, namely competition, collaboration, compromise, avoidance, and accommodating. Meanwhile, management satisfaction is in the "Very Good" category with 5 indicators, namely member satisfaction working in the organization, liking other members, perception of friendliness between members, willingness to cooperate with the organization again in the future, and perception of the satisfaction of other members in the organization. Based on the results of the product moment correlation test, the relationship between variables is moderate. Based on the results of a simple linear regression analysis, it was concluded that there was a positive and significant influence of the Conflict Management style on the satisfaction of the Student Institution Management at the Faculty of Social Sciences and Law, Universitas Negeri Makassar. This research is the first research at Makassar State University that discusses conflict management styles, especially in student institutions.